In silico structural analysis of Oryza sativa RAD51 reveals key interactions for nucleoprotein filament assembly and regulation - Ayesha Azeem; Syed Farhat Ali; Rana Salman Anjum (PLoS ONE, 2025)
Radiation sensitivity 51 (RAD51) is important for homologous recombination and DNA repair. The interaction between BRCA2 and RAD51 is crucial for the successful repair of DNA double strand breaks by homologous recombination. In the present study, through in silico analysis, we structurally characterized Os RAD51, a eukaryotic RAD51 ortholog from Oryza sativa Japonica A1 cultivar. Multiple sequence alignment showed the presence of conserved amino acids at the ATP- and DNA-binding sites. Several phosphorylation and ubiquitination sites were also predicted in Os RAD51 indicating its regulation by post-translational modifications. Structural modelling of Os RAD51 revealed two important regions at the protomer interface – one near the ATP-binding site (Walker A motif) and the other comprising of mainly hydrophobic residues. Polar and charge-charge interactions were noticeable at DNA- Os RAD51 interface of the modelled nucleoprotein filament. RAD51 assembly into the nucleoprotein filament is regulated by BRCA2. To study this interaction, Os RAD51 was modelled with O. sativa BRC repeats ( Os BRC). Os BRC was found to interact with Os RAD51 via hydrophobic and polar interactions. Moreover, structural analysis revealed that Os BRC interaction site overlap with the hydrophobic pockets of Os RAD51 required for protomer-protomer interaction, thus regulating the assembly of Os RAD51 into nucleoprotein filament. O. sativa BRCA2 ( Os BRCA2) was found to contain 8 BRC repeats. Os BRC repeats, similar to Homo sapiens BRC4 ( Hs BRC4), contained a conserved motif including a phenylalanine required for interaction with Os RAD51. So, Os BRCA2 can regulate the assembly of Os RAD51 through BRC repeats. The results of our study provide insights about structural basis of Os RAD51 nucleoprotein filament assembly and its regulation by BRCA2.